Cystatin C is associated with risk of venous thromboembolism in subjects with normal kidney function – the Tromsø study - Brodin, E. E.; Braekkan, S. K.; Vik, A.; Brox, J.; Hansen, J.-B. (Haematologica (Roma), 2012)
Previous studies have shown an association between impaired kidney function, assessed by cystatin C-based estimated glomerular filtration rate, and venous thromboembolism. The aim of this study was to investigate whether serum cystatin C was associated with a risk of venous thromboembolism among subjects with normal kidney function in a prospective population-based study. Cystatin C was measured in serum from 3251 men and women with normal kidney function, aged 25-84 years, who participated in the Tromsø study in 1994-1995. Normal kidney function was defined as a creatinine-based estimated glomerular filtration rate greater than 90 mL/min/1.73 m(2) and absence of microalbuminuria. Incident venous thromboembolism was registered from the date of inclusion through to the end of follow-up, September 1, 2007. Cox-regression models were used to calculate hazard ratios with 95% confidence intervals for venous thromboembolism. There were 83 incident venous thromboembolic events, of which 53 (63.9 %) were provoked, during a median of 12.3 years of follow-up. A one standard deviation (0.11 mg/L) increase in serum cystatin C levels was associated with a 43% (hazard ratio 1.43; 95% confidence interval 1.17-1.72) increased risk of total venous thromboembolism. Subjects with cystatin C levels in the top quartile (≥ 0.87 mg/L) had a 2.5-fold (hazard ratio 2.51; 95% confidence interval 1.27-4.96) increased risk of venous thromboembolism compared to those with levels in the bottom quartile (≤ 0.72 mg/L) in adjusted analysis. The risk estimates were even higher for provoked venous thromboembolism (hazard ratio 3.11; 95% confidence interval 1.23-7.86). Serum cystatin C levels were associated with the risk of venous thromboembolism in subjects with normal kidney function. Our findings suggest that elevated serum cystatin C levels may promote venous thrombosis beyond reflecting impaired kidney function.